PROBLEMATIKA PENANAMAN PENDIDIKAN AKHLAK PADA ANAK REMAJA NELAYAN TANJUNGBALAI - Nining Mulyani; Sapri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to identify the problems of instilling moral education in adolescent children of Tanjungbalai fishermen in Beting Kuala Kapias Sub-district, Teluk Nibung District and how efforts to overcome these problems. The method used is a qualitative method with the type of field research or field research. Data collection is done by conducting observation techniques, interviews and documentation studies. Based on the results of the study, the problems faced by parents are the lack of time parents have due to the busyness of parents going to sea, poor role modeling, the lack of role of community leaders, the less interesting activities of mosque youth so that it becomes the main factor that hinders the cultivation of moral education in fishermen adolescents.